1974
DOI: 10.1073/pnas.71.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transcription of hut DNA by Glutamine Synthetase

Abstract: The correct transcription of the hut (histidine utilization) operon DNA of Salmonella typhimurium requires activation either by 3':5'-cyclic adenosine monophosphate and catabolite-activating protein or by nonadenylylated glutamine synthetase (EC 6.3.1.2.). Thus, glutamine synthetase plays a regulatory role distinct from its enzymatic function.The synthesis of many degradative enzymes in bacteria is subject to catabolite repression. In the case of the enteric bacteria Escherichia coli, Salmonella typhimurium, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 19 publications
1
62
0
Order By: Relevance
“…In the absence of a carbon source that can be metabolized more readily than histidine, cyclic adenosine 3': 5'-monophosphate (cyclic AMP) and the cyclic AMPbinding protein activate transsription of hut genes which specify the enzymes for histidine catabolism. These genes are also activated by unadenylylated GS when histidine is the only available nitrogen source (Tyler et a/., 1974). Thus, catabolite repression of the hut operon is effectively reversed by NH,+-starvation, and NH,+-repression due to the lack of unadenylylated GS is reversed by depriving these bacteria of alternative carbon sources.…”
Section: ~~2 4mentioning
confidence: 80%
See 1 more Smart Citation
“…In the absence of a carbon source that can be metabolized more readily than histidine, cyclic adenosine 3': 5'-monophosphate (cyclic AMP) and the cyclic AMPbinding protein activate transsription of hut genes which specify the enzymes for histidine catabolism. These genes are also activated by unadenylylated GS when histidine is the only available nitrogen source (Tyler et a/., 1974). Thus, catabolite repression of the hut operon is effectively reversed by NH,+-starvation, and NH,+-repression due to the lack of unadenylylated GS is reversed by depriving these bacteria of alternative carbon sources.…”
Section: ~~2 4mentioning
confidence: 80%
“…In addition to its catalytic role and its postulated role as a repressor of GDH genes, unadenylylated GS protein activates transcription of Klebsiella genes that are involved in the metabolism of secondary nitrogen sources such as histidine and possibly elemental nitrogen (Tyler, Deleo & Magasanik, 1974;Tubb, 1974;Streicher et al, 1974). Not only was there a strong correlation between the activities of GS and nitrite reductase during continuous culture experiments in which nitrite was the only nitrogen source for growth (Cole et al,1g74), but also.mutants have been isolated that appear to be defective in the regulation of both of these proteins (Kavanagh & Cole, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these enzymes is stimulated by GS (3). In the case of the hut operon, coding for histidine-degrading enzymes, it has been shown that unadenylylated GS activates transcription of hut specific DNA (13).…”
Section: Discussionmentioning
confidence: 99%
“…The gal operon is subject to several different regulatory signals, and four different control sites at its operator-promoter region have been postulated (16). In an elegant study, Magasanik and his associates (17) have recently demonstrated that the two histidine utilization (hut) operons of Salmonella typhimurium require induction, but are also subject to positive regulatory signals relating to carbon and to nitrogen catabolite repression. These authors have shown that transcription of the hut operons requires activation by either cyclic AMP plus the catabolite-activating protein or by the nonadenylylated form of glutamine synthetase.…”
Section: Methodsmentioning
confidence: 99%